Kinetics of free and ligand-bound atacicept in human serum - Eslami, Mahya; Willen, Daniela; Papasouliotis, Orestis; Schuepbach-Mallpell, Sonia; Willen, Laure; Donzé, Olivier; Yalkinoglu, Özkan; Schneider, Pascal (Frontiers in Immunology, 2022)
BAFF (B cell activation factor of the TNF family / B lymphocyte stimulator, BLyS) and APRIL (a proliferation-inducing ligand) are targeted by atacicept, a decoy receptor consisting of the extracellular domain of TACI (transmembrane activator and calcium-modulator and cyclophilin (CAML) interactor) fused to the Fc portion of human IgG1. The purpose of the study was to characterize free and ligand-bound atacicept in humans. Total and active atacicept in serum of healthy volunteers receiving a single dose of subcutaneous atacicept or in patients treated weekly for one year were measured by ELISA, Western blot, or cell-based assays. Pharmacokinetics of free and bound atacicept were predicted based on total atacicept ELISA results. Persistence of complexes of purified atacicept bound to recombinant ligands was also monitored in mice. Results show that unbound or active atacicept in human serum exceeded 0.1 µg/ml for one week post administration, or throughout a 1-year treatment with weekly administrations. After a single administration of atacicept, endogenous BAFF bound to atacicept was detected after 8 h then increased about 100-fold within 2 to 4 weeks. Endogenous heteromers of BAFF and APRIL bound to atacicept also accumulated, but atacicept-APRIL complexes were not detected. In mice receiving intravenous injections of purified complexes pre-formed in vitro, atacicept-BAFF persisted longer (more than a week) than atacicept-APRIL (less than a day). Thus, only biologically inactive BAFF and BAFF-APRIL heteromers accumulate on atacicept in vivo. The measure of active atacicept provides further support for the once-weekly dosing regimen implemented in the clinical development of atacicept.